Directions For the Development of An Innovative Management System in The Context of Digital Transformation - Irina G. ERSHOVA; Olga S. PRIKHODCHENKO; Irina N. RODIONOVA; Elena S. SIMONENKO (Communications of International Proceedings, 2021)
Information and digital technologies are effective tools for the development of all spheres of society. In modern conditions, digital transformation is the key to the successful socio-economic development of the region. Digital technologies allow regional government bodies to effectively solve strategic management tasks and achieve the set goals of socio-economic development. The purpose of the study is to develop theoretical and methodological provisions for the formation of a digital system for managing the region's economy, built on the basis of a platform approach that ensures effective interaction between participants and allows solving strategic management tasks. The study is based on the use of methods of systemic and structural-functional approaches to the consideration of information resources, as well as general scientific methods of analysis and synthesis. This article discusses the goals and principles of project management in executive authorities. The role of a single information resource for planning and monitoring the execution of state programs and national projects of the Russian Federation in the digital transformation of the regional economic management system is revealed. On the basis of the study, the author proposes a platform approach as an effective mechanism for managing economic processes at the regional level. Active processes of digital transformation are changing the architecture of the regional economic management system. The functioning of the system of strategic management of the region's economy presupposes the creation of an information and analytical model based on the use of a set of information and digital technologies.
Keywords: Regional Economy Management; Project Management; Digital Transformation; Digital Technologies; Platform Approach.